2018
DOI: 10.1159/000490181
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Skin Prick Tests to Latex and Patch Tests to Rubber Additives and other Causative Factors among Dental Professionals and Students with Contact Dermatoses

Abstract: Background: Dental workers often experience unwanted allergic and nonallergic skin reactions resulting in different contact dermatoses (e.g., contact urticaria, irritant and allergic contact dermatitis) that are often attributed to rubber gloves. Objective: To examine allergic and nonallergic contact dermatoses by different methods amongst dental professionals and dental students, more specifically, reactions to natural rubber latex (NRL), rubber additives, and other causative factors. Methods: In this cross-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 18 publications
2
32
0
Order By: Relevance
“…There was an increase in Type I latex allergy in healthcare workers in the late 1980s and early 1990s, due to the increased demand for latex protective gloves and poor manufacturing control. The introduction of low‐protein powder‐free latex gloves over recent years has resulted in reduced exposure in healthcare workers to latex antigens, and served to prevent sensitization to NRL (natural rubber latex) . Nitrile rubber gloves do not cause immediate‐type allergy but may contain important contact allergens such as carbamates, thiurams, or mercaptobenzothiazoles, which may cause allergic contact dermatitis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was an increase in Type I latex allergy in healthcare workers in the late 1980s and early 1990s, due to the increased demand for latex protective gloves and poor manufacturing control. The introduction of low‐protein powder‐free latex gloves over recent years has resulted in reduced exposure in healthcare workers to latex antigens, and served to prevent sensitization to NRL (natural rubber latex) . Nitrile rubber gloves do not cause immediate‐type allergy but may contain important contact allergens such as carbamates, thiurams, or mercaptobenzothiazoles, which may cause allergic contact dermatitis .…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of low-protein powder-free latex gloves over recent years has resulted in reduced exposure in healthcare workers to latex antigens, and served to prevent sensitization to NRL (natural rubber latex). [24][25][26] Nitrile rubber gloves do not cause immediate-type allergy but may contain important contact allergens such as carbamates, thiurams, or mercaptobenzothiazoles, which may cause allergic contact dermatitis. 27 In our study, immediate and delayed skin reactions were not differentiated based on the questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most commonly mentioned allergens is rubber, which can be found in latex gloves (worn by dentists and their assistants) and rubber dams (used to isolate the operative site from the rest of the mouth) [17][18][19] . Cases of adverse patient reactions to latex gloves worn by dental health care workers have been reported by Agrawal et al Their study results showed that 16% of dental professionals reported allergy to latex gloves, with the prevalence significantly higher in those who had allergy to pollen grains, foodstuffs and rubber dam, asthma and eczema in their medical history 17 .…”
Section: Oral and Perioral Diseases Related To Allergic Reactions Andmentioning
confidence: 99%
“…during dental treatment (when dentist's glove comes in contact with the lip, or in contact with cinnamaldehyde, menthol or eugenol in toothpaste), etc. 18,19 . In dental practice, also possible are allergic reactions to formaldehyde (used for disinfection in root canals), immediate-type allergies to local anesthetics or delayed-type allergies from longer operative procedures (e.g., additives from the glove rubber or rubber dam) 1,7 .…”
Section: Review Of Oral and Perioral Diseases And Causative Allergensmentioning
confidence: 99%
“…The introduction of low protein powder-free latex gloves over recent years resulted in a reduction of the exposure of healthcare workers to latex antigens, and served to prevent sensitization to NRL (natural rubber latex). [14][15][16] Dental students pointed out plastics as the major cause for adverse respiratory reactions. Plastic materials used in dentures are based on acrylic resins.…”
Section: Discussionmentioning
confidence: 99%